(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
Today, in the education of students, attention is mainly focused on the acquisition of knowledge and methods, but sufficient attention is paid to mastering the secrets of human relations and mutual professional activities. In practice, the ability to work with people is defined as the most important factor in the success of any modern professional. The very process of formation and development of the sphere of communication should be complex, since it allows for closer integration with other professional disciplines.